Dimensionamento de reservatorio de contenção na Bacia do Rio Lonqueador para mitigação de inundação na área urbana de Francisco Beltrão - Steinhorst, Camila Daiane Cancelier (2022)
The irregular outward growth of cities, caused by new neighborhoods risings, reduces the natural vegetation landscapes, parks areas, woods and stream banks, contributing to increase soil sealing areas. The soil sealing process reduces water infiltration into the soil and increases the volume and speed of surface runoff, as well as the likelihood of urban flooding, erosion and siltation. In order to mitigate the impact caused by the soil sealing in these areas, the city of Francisco Beltrão is carrying out works in order to increase the existent inlets streams and the slope of them in the urban perimeter to reduce the occurrence of flood events in a recurrence time of 100 years period, however the developed projects currently are not concerned to Lonqueador River watershed. This work presents a study of the implementation of 5 flood retention reservoirs at the present watershed. The sections flow of Lonqueador River where the channel inlet is reduced and restricts the flow was estimated and used as a limit for the effluent flow from the reservoirs. The intense rainfall considered for the study was estimated by the IDF Equation, distributed in temporal seasons of rainfall by the Huff method and its surface runoff separated by the SCS method to determine the triangular synthetic unit hydrograph and the hydrograph design. The sizing of each proposed retention reservoir was performed using the Puls method with the input parameters: project hydrograph, elevation x reservoir volume curve and elevation x flow curve of the bottom spillway. The restriction flow of the R03 reservoir of 13.6 m3/s contributed to get a greater volume and height of water stored in sizing, 138136 m3 and 20.77 m. For the existing reservoir R04, a volume of 16209 m3 and the reduction of the section of its bottom spillway with 0.40-meter diameter concrete pipes are required. In the R05 reservoir, it is required a storage of only 14109 m3 and 3 bottom spillways with 1 meter diameter tubes, in addition to the crest spillway. It was concluded that the installation of the containment reservoirs R03, R04 and R05 contributes to the mitigation of floods in the urbanized area for a recurrence time of 100 years, without the need to implant the reservoirs R01 and R02.